دور استراتيجيات التفكير الإبداعي في تعزيز الميزة التنافسية في مؤسسات التعليم العالي(دراسة ميدانية في جامعة تشرين) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدف البحث إلى التعرّف على العلاقة بين استراتيجيات التفكير الإبداعي وتعزيز الميزة التنافسية في جامعة تشرين، من خلال تحديد مدى تأثير كل من أبعاد استراتيجيات التفكير الإبداعي والأساليب المتبعة لتطبيق هذه الاستراتيجيات، على خصائص المورد البشري، وتوفر الكفاءات المتميزة، وقد اعتمدت الباحثة على المقاربة الاستنباطية وعلى المنهج الوصفي كمنهج عام للبحث، وقامت بتوزيع الاستبيان على 350 فرد من أعضاء الهيئة التعليمية ورؤساء الشعب العاملين في جامعة تشرين، وقد خلصت هذه الدراسة إلى عدة نتائج، كان أهمها وجود علاقة معنوية بين استراتيجيات التفكير الإبداعي وتعزيز الميزة التنافسية، ولكن هذه العلاقة ضعيفة، ويعود السبب في ذلك إلى ضعف برامج التدريب المتبعة، وخاصةً في مجال التفكير الإبداعي، وقد استعرضت الباحثة العديد من النتائج الهامة في نهاية هذا البحث، كما قدّمت العديد من المقترحات والتوصيات، والتي كان أهمها: ضرورة قيام الجامعة بإجراء دورات تدريبية للعاملين فيها، خاصة بتنمية مهارات التفكير الإبداعي، وتعريف العاملين لديها بأهمية استخدام استراتيجيات التفكير الإبداعي ضمن أعمالهم، من أجل تنمية مهاراتهم ومعارفهم بما ينعكس على تطوير أدائهم بالشكل الذي يمكن من تعزيز الميزة التنافسية.The research aimed to identifying the relationship between the creative thinking strategies and enhancing the competitive advantage in Tishreen university. By identifying the extent of the impact of each dimensions of creative thinking strategies and the methods used to implement these strategies on the human resource characteristic and distinctive competencies. The researcher relied on the Deductive Approach and on the descriptive approach as a general method. She has distributed the questionnaire to 350 people, they are members of the teaching staff and the heads of section, who work in Tishreen university. This study has concluded to several results, the most important one was that there were significant relationship between creative thinking strategies and enhancing the competitive advantages. But this relationship is weak, because of the weakness of training programs, especially in the field of creative thinking. The researcher reviewed many important results at the end of this research, and also presented several proposals and recommendations, and the most important of it was: the need of the university to conduct training courses for their employees, especially for development creative thinking skills, and definite their employees to the important of using creative thinking strategies in their work, in order to develop their skills and knowledge as the reflect on the develop of their performance, and enhance the competitive advantages.